Colorectal Cancer Cell-Derived Small Extracellular Vesicles Educate Human Fibroblasts to Stimulate Migratory Capacity - Clerici, Stefano Piatto; Peppelenbosch, Maikel; Fuhler, Gwenny; Consonni, Sílvio Roberto; Ferreira-Halder, Carmen Veríssima (Frontiers in Cell and Developmental Biology, 2021)
Colorectal cancer (CRC) is in the top ten cancers most prevalent worldwide affecting equally men and women. Current research on tumor-derived extracellular vesicles (EVs) suggests that these small extracellular vesicles (sEVs) play an important role mediating cell-to-cell communication and thus potentially affecting cancer progression via multiple pathways. In the present study, we hypothesized that sEVs derived from different colorectal cancer cell lines differ in their ability to reprogram normal human fibroblasts through a process called tumor education. The sEVs derived from CRC cell lines (HT29 and HCT116) were isolated by a combination of ultrafiltration and polymeric precipitation, followed by characterization based on morphology, size, and the presence or absence of EVs and non-EVs markers. It was observed that the HT29 cells displayed a higher concentration of sEVs compared to HCT116 cells. For the first time, we demonstrated that HT29-derived sEVs were positive for Lmwptp. CRC cell-derived sEVs were uptake by human fibroblasts stimulating migratory ability via Rho-Fak signaling in co-incubated human fibroblasts. Another important finding showed that HT29 cell-derived sEVs are much more efficient in activating human fibroblasts to CAFs. Indeed, the sEVs produced by HT29 cell line that are less responsive to cytotoxic agent, display higher efficiency in educating normal human fibroblasts by providing them advantages such as activation and migratory ability. In other words, these sEVs have an influence on the CRC microenvironment, in part, due to reprogramming fibroblasts.